Modern trends in diseases of the ear, nose and throat - Ellis, Maxwell (Butterworths medical publications. Modern trends series., 1954)
Modern Trends in Diseases of the Ear, Nose, and Throat presents a critical review of speech therapy for children with cleft palate. The book discusses the development and treatment of cancer of the larynx, as well as the condition of a patient after laryngectomy. Some of the topics covered in the text are the radiology of the ear, nose, and throat; the description of the pharyngeal diverticulum and laryngeal paralysis; and the mechanisms of larynx stenosis. The development of tuberculosis of the upper air passages; the physiology of the esophagus; and the diagnosis of facial paralysis are also.